2021
DOI: 10.1055/s-0041-1735598
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco and Its Ill-Effects: Recent Literature Update

Abstract: According to the Global Adult Tobacco Survey part 2 (GATS-2), approximately 200 million adult Indians consume smokeless tobacco (SLT). Circumvention of SLT product ban has been observed. We conducted a review of the literature to summarize the ill effects of tobacco for the articles published from 2019 to 2020. A systematic search of the databases PubMed (2019 onward) and Web of Science (2019 onward), through February 2021 was done. Search yielded 1,061 articles and after excluding articles based on the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This aligns with the findings of Muthukrishnan and Warnakulasuriya 12 , who identified increased gutkha use as the most common cause of OSMF in India. Singhavi et al 14 also found that gutka was the most commonly consumed SLT product leading to OSMF in India. Another study by Vellappally et al 15 demonstrated that the most prevalent form of SLT consumed was a black powder known as "misri," obtained by roasting and powdering tobacco, and was applied by rubbing it on the gums.…”
Section: Discussionmentioning
confidence: 97%
“…This aligns with the findings of Muthukrishnan and Warnakulasuriya 12 , who identified increased gutkha use as the most common cause of OSMF in India. Singhavi et al 14 also found that gutka was the most commonly consumed SLT product leading to OSMF in India. Another study by Vellappally et al 15 demonstrated that the most prevalent form of SLT consumed was a black powder known as "misri," obtained by roasting and powdering tobacco, and was applied by rubbing it on the gums.…”
Section: Discussionmentioning
confidence: 97%
“…38,39 24 states and 3 union territories banned gutkha (SLT) by May 2013. 40 However, it is inconsistently enforced. A Mumbai study found that marketers circumvent legislation through twin packaging, flavouring tobacco, and areca nut.…”
Section: Government Policies For Risk Factor Preventionmentioning
confidence: 99%